2020
DOI: 10.32479/ijefi.10136
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Audit Quality, Audit Committee and Financial Reporting Quality: Evidence From Malaysia

Abstract: In recent decades, there has been a noticeable increase in the practice of earnings management (EM) as a proxy for financial reporting, especially real activities, with effect on the quality of financial statements. The role of the audit committee in mitigating EM remains ambiguous because of inconclusive findings. Therefore, this study examines the moderating effect of audit quality and audit committee on financial reporting quality, also known as real earnings management in Malaysian companies. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
54
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 36 publications
14
54
0
6
Order By: Relevance
“…Our findings are consistent with literature as most studies reported positive significant association between ACMEET and FRQ measured in various proxies (Habbash & Alagla, 2015;Hamdan, 2020;Hasan et al, 2019;Hasan et al, 2020;Lin et al, 2006;Mwangi, 2018;Shankaraiah & Amiri, 2017). Our results confirmed the findings of previous studies as more AC meetings is positively affected FRQ.…”
Section: Multivariate Analysis (Regression Analysis and Hypotheses Testingsupporting
confidence: 93%
“…Our findings are consistent with literature as most studies reported positive significant association between ACMEET and FRQ measured in various proxies (Habbash & Alagla, 2015;Hamdan, 2020;Hasan et al, 2019;Hasan et al, 2020;Lin et al, 2006;Mwangi, 2018;Shankaraiah & Amiri, 2017). Our results confirmed the findings of previous studies as more AC meetings is positively affected FRQ.…”
Section: Multivariate Analysis (Regression Analysis and Hypotheses Testingsupporting
confidence: 93%
“…H5: There is a significant positive relationship between audit committee independence and FRQ (Hasan et al, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…This characteristic of the audit committee has received considerable attention in the previous literature that indicates a positive relationship between audit committee financial, accounting expertise, and FRQ (Alzeban 2019;Hassan 2011;Nuraini 2015). In contrast, some studies have found an insignificant relationship which argues that having a financial expert in the audit committee is not enough component for improving the quality of financial information (Hasan et al, 2020;Kibiya et al, 2016). According to Shankaraiah et al (2017), some accounting experts in the audit committee assess the subjective judgments of the management, meet more frequently, and more often disagree with the financial reporting decisions of the management, and finally result in inadequate monitoring over the reporting process.…”
Section: Empirical Evidence Between Corporate Governance and Frqmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary role of an auditor is to clarify professionally and reasonably whether financial statements prepared by the companies provide objective and reliable information. Audit quality increases financial reporting quality by improving investors' confidence (Hasan et al, 2020). In addition, audit quality may mitigate problems appearing from information asymmetry (Dobler, 2008).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%